Вплив снігового покриву і лавин на розвиток гірськолижного туризму в Буковинських Карпатах - Круль, Галина Ярославівна; Паламарюк, Марія Юріївна (Видавничо-поліграфічне підприємство "МІСТО", 2020)
The impact of snow cover and avalanches on the development of recreational tourism and recreation are discussed in the article. Long-term observations of the duration and height of snow cover were analyzed. The most favorable slopes for the development of ski tourism have northern and northeastern exposure. The slopes of the Bukovynian Carpathians have been identified, where it is not recommended to develop ski tourism. The degree of avalanche danger in the Bukovynian Carpathians depends on the size of avalanches and their recurrence. The reasons for the indensification of avalanche activity are given in the publication. Based on the zoning of the Ukrainian Carpathians according to the degree of avalanche danger, in the territory of the Bukovynian Carpathians there are two areas: medium and low avalanche danger.
Keywords: сніговий покрив; рельєф; лавинна небезпека